Involucrella lithophila (Rubiaceae: Spermacoceae): A new species from Guangxi, China - Yuan, Ming-Deng; Wang, Rui-Jiang (Phytotaxa, 2020)
Involucrella lithophila from the limestone area of Guangxi, China, is described and illustrated here. It is most similar to Hedyotis kurzii and Involucrella chereevensis in having tetragonal stems, slender pedicels and loculicidally dehiscent capsules, but it differs from the former by its 3–5 (–7)-lobed stipules, heterostylous and white flowers and depressed seeds, and from the latter by its 2–4 secondary leaf veins and heterostylous flowers. The molecular phylogenetic analysis revealed that this new species was embedded in the Involucrella clade and closely related to I. chereevensis. It is evaluated as Least Concern according to IUCN Red List Categories and Criteria.